The Effectiveness of M-Health on Self-Efficacy, Self-Management, and Self-Care of Patients Undergoing Maintenance Hemodialysis: A Systematic Review and Meta-Analysis - Hardhanti, Rizqi; Erna Rochmawati (Universitas STRADA Indonesia, 2026)
Background: M-Health is the use of mobile digital technology to support health and well-being by extending education, communication, health interventions, and research beyond the reach of traditional clinical care. Research has developed and tested M-Health, demonstrating its effectiveness in enhancing the self-efficacy of cancer patients. However, there has been no synthesis on the effectiveness of M-Health in enhancing self-efficacy in patients with chronic kidney disease. Purpose: The purpose of this systematic review and meta-analysis is to determine the effectiveness of M-Health on self-efficacy, self-management, and self-care in chronic kidney disease patients undergoing maintenance hemodialysis. Methods: The study method is a systematic review and meta-analysis reported according to PRISMA guidelines. We conducted this systematic review across six databases. We included randomized controlled trials, quasi-experimental studies, and cohort studies evaluating self-efficacy, self-management, and self-care in patients with chronic kidney disease. We performed the critical appraisal using the Joanna Briggs Institute Critical Appraisal Checklist. Review Manager version 4.5 synthesized the data. Results: In this study, a database search was conducted to obtain 1,115 articles. Then, 46 duplicates were identified, and 1,109 articles were excluded for not meeting the inclusion criteria, leaving 6 articles for review. After reviewing the six articles, M-Health was found to be effective for self-efficacy and self-management, but not for self-care, due to the study's short duration. Conclusion: The conclusion of this study is that M-Health intervention can improve self-efficacy and self-management in patients with chronic kidney disease. However, the effectiveness of self-care results is reduced due to the relatively short observation time. Therefore, it is essential to take into account the duration of the intervention to achieve more optimal outcomes.